Cultural continuity between the Camanchaco-Chango Paposins families during the XVIII and XIX centuries, through the analysis of the social category of the “aggregate” - Castelleti D., José (Universidad Católica del Norte, Instituto de Investigaciones Arqueológicas y Museo, 2019)
Significant ethnographic information rescued by the paposins researchers Lazo and Gutiérrez (Lazo y Téllez, 1984; Gutiérrez y Lazo, 1996), allows to interpret the historical conditions that have defined the Camanchaca or Chango families of the Paposo/Taltal coast during the XVIII and XIX centuries, with the presence of the social and parental category of the "aggregates" or "relatives", subjects coming from the southern Altiplano or from other coastal groups, who were integrated into the local families from "compadrazgos" or commercial relationships (Larraín and Bugueño, 2011). The configuration of behaviors or habitus is discussed here (sensu Bourdieu, 1980), which this category of the "aggregate" would have generated among the Camanchaca or Chango families, also discussing how much of this social landscape is related to moments of contact and pre-hispanic, defining cultural continuity. To this end, such categorizations have been critically tracked between the material and oral information sources related to the Camanchaca/Chango occupation, in order to evaluate their probable causes and the way in which local and non-coastal individuals articulated themselves in the increasing exchange of charquecillo from pre-hispanic times, specialized behavior that will be marketed by the spanish crown and later by the national states.